2001
DOI: 10.1093/occmed/51.3.174
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposures to metals, solvents and pesticides: recent evidence on male reproductive effects and biological markers

Abstract: This review is based primarily on the recent epidemiological studies conducted in occupational settings in order to explore the relationship between exposures to chemical agents and the possible effects on male reproductive function. The paper examines evidence of the effects of metals, solvents, pesticides and dioxin. The effects considered are primarily the possible alterations of sperm quality and reduction of fertility. Many studies have identified small groups of workers with exposures to these agents, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 65 publications
0
44
0
Order By: Relevance
“…Although the sitting position may cause increase of scrotal temperature, this increase seems not strong enough to disrupt spermatogenesis that may recover during other parts of the day [13,14]. Research during past 25 years has identified a large number of chemicals and occupational exposures that may impair male fertility (Table 1) [15][16][17][18][19][20][21][22][23][24][25][26]. It should, however, be acknowledged that epidemiological studies of male fertility and semen quality are beset with a number of pitfalls and methodological limitations crude exposure assessment, low participation rates, inadequate study size and lacking quality assurance of the semen analysis [27,28].…”
Section: Occupational Hazardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the sitting position may cause increase of scrotal temperature, this increase seems not strong enough to disrupt spermatogenesis that may recover during other parts of the day [13,14]. Research during past 25 years has identified a large number of chemicals and occupational exposures that may impair male fertility (Table 1) [15][16][17][18][19][20][21][22][23][24][25][26]. It should, however, be acknowledged that epidemiological studies of male fertility and semen quality are beset with a number of pitfalls and methodological limitations crude exposure assessment, low participation rates, inadequate study size and lacking quality assurance of the semen analysis [27,28].…”
Section: Occupational Hazardsmentioning
confidence: 99%
“…In 1995 the US Institute of Medicine Committee stated that "the prevailing view is that exposure of the human male to chemicals and ionizing radiation is generally unrelated to the occurrence of developmental endpoints such as miscarriage, birth defects, growth retardation and Table 1. Chemical and physical exposures that have been associated with reduced semen quality or impaired male fertility (for systematic reviews, see [15][16][17][18][19][20][21][22][23][24][25][26] npg cancer" [56]. The question is, however, whether lack of convincing examples of male mediated developmental toxicity in humans is due to the non-existence of this phenomenon due to huge methodological challenges in demonstrating effects.…”
Section: Male Mediated Development Toxicitymentioning
confidence: 99%
“…Occupational activities involving exposure to specific chemicals or expositions to toxicants may impair male reproductive health and cause infertility in humans [27,37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity and smoking are thought to be some of the most critical among these factors [4][5][6][7][8][9][10][11][12][13][14][15][16]. It has also been established that some drugs, heavy metals and solvents, may affect fertility [17][18][19]. However, there is relatively little data regarding IVF success depending on the type of area inhabited by the patient [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%